Polityka Unii Europejskiej wobec krajów rozwijających się w kontekście przystąpienia do niej Polski - Czernichowski, Konrad (European Union's Policy towards Developing Countries after Poland's Joining the European Union, 2006)
Before joining the European Union, Poland hardly gave any funds for developing infrastructure in poor countries. The article deals with the forms and the range of such aid in the EU. Although this policy is not coordinated to a big extent, it can have a significant impact on the relations of Poland with LDC (the least developed countries). The most important agreement between the EU and developing countries, which ties also Poland down, is the Cotonou Agreement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 124-137